On the enhanced wear resistance of laser-clad CoCrCuFeNiTix high-entropy alloy coatings at elevated temperature. (October 2022) - Huang, Yubin; Hu, Yongle; Zhang, Mingjun; Mao, Cong; Tong, Yonggang; Zhang, Jian; Li, Kangwei; Wang, Kaiming
Abstract: One major hindrance that high-temperature working components face nowadays is wear. The CoCrCuFeNiTix (x = 0, 0.5, 1.0 and 1.5) high-entropy alloy coatings were synthesized on 45 steel substrates via laser cladding to prolong the service life of engineering components under high-temperature working conditions. The microstructure and 600 °C tribological properties of the coatings were systematically investigated. Ti addition facilitated the precipitation of hard phases (i.e., Laves phase and Ti-rich phase) and refined the grains. The formation of a protective TiO2 layer on the worn surface of CoCrCuFeNiTi1.5 coating inhibited abrasion and oxidative wear, contributing to the lowest wear rate. The enhanced wear resistance of CoCrCuFeNiTi1.5 coating at elevated temperature benefited from the synergistic effect of improved microhardness and oxidation resistance.